1995
DOI: 10.1007/bf03165003
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral blood flow, blood volume, oxygen extraction fraction, and oxygen utilization rate in normal volunteers measured by the autoradiographic technique and the single breath inhalation method

Abstract: By means of a high resolution PET scanner, the regional cerebral blood flow (rCBF), cerebral blood volume (rCBV), oxygen extraction fraction (rOEF), and metabolic rate of oxygen (rCMRO2) for major cerebral gyri and deep brain structures were studied in eleven normal volunteers during an eye-covered and ear-unplugged resting condition. Regional CBF was measured by the autoradiographic method after intravenous administration of H2(15)O. Regional OEF and rCMRO2 were measured by the single inhalation of 15O2. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
72
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 19 publications
11
72
4
Order By: Relevance
“…[31][32][33][34][35] The meta-analysis was composed of CMR O2 and CMR glc values from as few as 23 and as many as 46 distinct brain areas in 109 subjects. BioImage Suite (www.…”
Section: Regional Oxidative Demand For Glutamatergic Activity In the mentioning
confidence: 99%
“…[31][32][33][34][35] The meta-analysis was composed of CMR O2 and CMR glc values from as few as 23 and as many as 46 distinct brain areas in 109 subjects. BioImage Suite (www.…”
Section: Regional Oxidative Demand For Glutamatergic Activity In the mentioning
confidence: 99%
“…However, Iida et al (1993) have estimated the amount of recirculating water and showed that its amount can be predicted using a single compartment model in three-step ARG in normal human subjects. This method eliminates the need for plasma separation and simplifies the PET procedure (Hatazawa et al, 1995;Shidahara et al, 2002). However, as this method depends on intersubject variation of the arterial 15 O 2 TAC (which yields a bias in the CMRO 2 in DARG), its validity requires further evaluation in human studies.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative autoradiographic method (ARG) using only short administration times for each of the three tracers (three-step ARG) has been developed (Mintun et al, 1984) and subsequently simplified and optimized (Iida et al, 1993;Sadato et al, 1993;Hatazawa et al, 1995;Shidahara et al, 2002;Hattori et al, 2004). Cerebral blood flow images can be obtained by an H 2 15 O autoradiographic method, using a PET counts-versus-CBF nomogram, which follows a simple look-up table procedure Herscovitch et al, 1983;Kanno et al, 1987); the quantitative accuracy of these images is improved when input delay and dispersion are corrected (Iida et al, 1986(Iida et al, , 1988.…”
Section: Introductionmentioning
confidence: 99%
“…The [HHb] increase (54 mmol×l 71 ) found in this study is very small (4 ± 6%) compared to the estimated total blood volume of approximately 70 ± 100 mmol×l 71 in the cerebrum. 24 Levine et al 25 also reported a small decrease in cerebral¯ow during orthostatic challenges in able-bodied individuals using transcranial Doppler. Although MAP and consequently cerebral perfusion pressure decreased more in SCI than AB, the [HHb] decrease was similar in both groups.…”
Section: Cerebral Oxygenation Changementioning
confidence: 95%